Antibacterial efficacy of bioceramic root canal sealers against planktonic Enterococcus faecalis after different contact and setting time: An in vitro study - Marija Simundic Munitic; Sandra Marijan; Darko Kero; Ivona Bago (Wolters Kluwer Medknow Publications, 2022)
Introduction: Bioceramic root canal sealers are the newest generation of root canal sealers. Τhere are contradictory results in the literature about their antimicrobial activity. The aim of the study was to evaluate the antimicrobial efficacy of four root canal sealers against Enterococcus faecalis. Materials and Methods: Four root canal sealers were used in order to examine antibacterial efficacy: TotalFill, BioRoot Root Canal Sealer, mineral trioxide aggregate (MTA) Fillapex, and AH Plus. The bacterial suspension was placed on a freshly mixed sealer, one or 3 days set sealer in vertically held microtiter plates. After incubation of 2, 5, 20, and 60 min in 100% humidity at 37 C, Trypticase Soy Broth was added to each well and mixed. Then, bacterial suspension from each well was transferred, serially diluted, and placed on Mitis salivarius agar plates. After incubation, colony-forming units were counted. All experiments were performed in triplicate. The outcomes of antimicrobial properties of tested materials were analyzed by one-way analysis of variance. Results: All bioceramic root canal sealers showed significantly better efficacy than the control group and epoxy resin sealer (P < 0.05). TotalFill presented the highest efficacy comparable with BioRoot RCS (P > 0.05), followed with MTA Fillapex (P < 0.05). Also, freshly mixed sealers showed comparable efficacy as sealers set for 3 days (P > 0.05), but better than sealers set for 1 day (P < 0.05). All sealers exhibited the highest efficacy after 20 min of contact time, independently of materials that were freshly mixed or set for 1 or 3 days. Conclusion: Bioceramic sealers have greater antimicrobial activity than commercially used epoxy resin sealer. These sealers exhibited the strongest efficacy at 20 min of contact time, independently of their setting condition.